2018
DOI: 10.1038/s41594-018-0112-y
|View full text |Cite
|
Sign up to set email alerts
|

RNA polymerase II clustering through carboxy-terminal domain phase separation

Abstract: The carboxy-terminal domain (CTD) of RNA polymerase (Pol) II is an intrinsically disordered low-complexity region that is critical for pre-mRNA transcription and processing. The CTD consists of hepta-amino acid repeats varying in number from 52 in humans to 26 in yeast. Here we report that human and yeast CTDs undergo cooperative liquid phase separation, with the shorter yeast CTD forming less-stable droplets. In human cells, truncation of the CTD to the length of the yeast CTD decreases Pol II clustering and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

36
507
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 515 publications
(545 citation statements)
references
References 60 publications
(16 reference statements)
36
507
1
1
Order By: Relevance
“…Such interactions retain a larger conformational flexibility compared to interactions through complementary protein domain surfaces and induced fit (Aguzzi & Altmeyer, 2016;Boeynaems et al, 2018). Moreover, phase separation occurs at gene promoters and super-enhancers (Boehning et al, 2018;Boija et al, 2018;Lu et al, 2018;Sabari et al, 2018). Moreover, phase separation occurs at gene promoters and super-enhancers (Boehning et al, 2018;Boija et al, 2018;Lu et al, 2018;Sabari et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such interactions retain a larger conformational flexibility compared to interactions through complementary protein domain surfaces and induced fit (Aguzzi & Altmeyer, 2016;Boeynaems et al, 2018). Moreover, phase separation occurs at gene promoters and super-enhancers (Boehning et al, 2018;Boija et al, 2018;Lu et al, 2018;Sabari et al, 2018). Moreover, phase separation occurs at gene promoters and super-enhancers (Boehning et al, 2018;Boija et al, 2018;Lu et al, 2018;Sabari et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Besides the nucleolus, nuclear speckles, and RNA granules, also silent heterochromatin domains were recently shown to phase separate within the nucleus (Larson et al, 2017;Strom et al, 2017). Moreover, phase separation occurs at gene promoters and super-enhancers (Boehning et al, 2018;Boija et al, 2018;Lu et al, 2018;Sabari et al, 2018). To which extent other chromatin domains rely on phase separation for their spatio-temporal confinement and for their biological functions is a matter of intense investigation.…”
Section: Introductionmentioning
confidence: 99%
“…It is presently unknown how various multivalent interactions acting together results in self-organization. However, LLPS-like processes likely influence the organization and interaction of most cellular macromolecules, exemplified by the recent evidence that eukaryotic transcription systems, including genome interaction hubs, exhibit selforganizing attributes (Boehning et al, 2018;Cho, Spille, Hecht, et al, 2018;Chong et al, 2018;Lu et al, 2018;Sabari, Dall'Agnese, Boija, et al, 2018). This review will focus on the reported functional architecture of the larger (>1 μm) and well-documented nuclear bodies, such as nucleoli, paraspeckles, and nuclear speckles ( Figure 2).…”
mentioning
confidence: 99%
“…Super‐enhancers are thought to facilitate cancer development by driving a higher transcriptional output of prominent oncogenes . Recent studies demonstrate that IDR‐containing transcription factors, transcriptional coactivators (eg, Mediator complex and Mediator‐associated BRD4) and RNA Polymerase II phase‐separate in vitro . These proteins also assemble liquid‐like condensates at super‐enhancer target genes, activating their expression.…”
Section: Biomolecular Condensates In Cancermentioning
confidence: 99%